Programa multiprofissional de acolhimento familiar : uma construção coletiva na unidade de terapia intensiva neonatal - Souza, Bruna Gomes de (2024)
Introduction: The Neonatal Intensive Care Unit is considered an unwelcoming and stressful environment for families of hospitalized newborns, therefore, multidisciplinary programs aimed at these families help them positively in coping with stressful situations during hospitalization. The Family Centered Care guidelines guide a humanized and welcoming care practice. Aiming to meet the institutional demand for improvements and advances in care, this study was developed in collaboration with the unit's multidisciplinary team. General objective: Structure a multidisciplinary family fostering program. Method: Participatory research in the action research category according to Thiollent (2011), to structure and validate the multidisciplinary program and its guiding technologies. It was developed in the Neonatal Intensive Care Unit of the Hospital Universitário do Espírito Santo. The members of the multidisciplinary team were the collaborators in the study, where 14 specialists including managers and multidisciplinary routine formed the working group in the structuring stage. In the validation stage, 65 experts from the multidisciplinary team validated the protocol, 13 the program, and 11 the educational technology. Qualitative data were collected in 5 seminars, recorded in MP3 and MP4 audio, transcribed and recorded in a field diary, being analyzed following Bardin's content analysis technique (2016). The evaluation instruments followed the evaluation criteria proposed by Pasquali (2010). In the analysis of quantitative data, the Cronbach's alpha coefficient was used to check reliability, the Fleiss Kappa coefficient to measure agreement, and the Content Validity Index to check relevance and representativeness. Results: The program was built collectively, and the actions of the multidisciplinary team for family support are related to the provision of a reference team, assessment of family needs, holding support groups and counseling for parents, insertion of the family in decision-making and care for the family. newborn, control of light and noise, offering therapeutic workshops and medical report, assessment of family satisfaction, and strategies for communicating difficult news and support for neonatal grief. The technologies built were validated by experts. In the reliability assessment, Cronbach's Alpha reached values above 0.90, excellent reliability. There were variable agreements between substantial/perfect and significant (k=0.68 to k=1.00; p90.0%). Products: Program, Protocol, Flowcharts, Forms, Standard Operating Procedures, Educational Instruments, and Educational Technology of the Primer type. Conclusion: The Multidisciplinary Family Care Program and its guiding technologies were collectively constructed with the neonatal multidisciplinary team and validated with high levels of reliability and agreement, being considered relevant and representative by experts